Adjuvant gemcitabine therapy improves survival in a locally induced, R0-resectable model of metastatic intrahepatic cholangiocarcinoma - Gürlevik, Engin; Longerich, Thomas (Hepatology, 2013)
Complete surgical tumor resection (R0) for treatment of intrahepatic cholangiocarcinoma (ICC) is potentially curative, but the prognosis remains dismal due to frequent tumor recurrence and metastasis after surgery. Adjuvant therapies may improve the outcome, but clinical studies for an adjuvant approach are difficult and time-consuming for rare tumor entities. Therefore, animal models reflecting the clinical situation are urgently needed to investigate novel adjuvant therapies. To establish a mouse model of resectable cholangiocarcinoma including the most frequent genetic alterations of human ICC, we electroporated Sleeping Beauty-based oncogenic transposon plasmids into the left liver lobe of mice. KRas-activation in combination with p53-knockout in hepatocytes resulted in formation of a single ICC nodule within 3-5 weeks. Lineage tracing analyses confirmed the development of ICC by transdifferentiation of hepatocytes. Histologic examination demonstrated that no extrahepatic metastases were detectable during primary tumor progression. However, formation of tumor satellites close to the primary tumor and vascular invasion were observed, indicating early invasion into normal tissue adjacent to the tumor. After R0-resection of the primary tumor, we were able to prolong median survival, thereby observing tumor stage-dependent local recurrence, peritoneal carcinomatosis, and lung metastasis. Adjuvant gemcitabine chemotherapy after R0-resection significantly improved median survival of treated animals. Conclusion: We have developed a murine model of single, R0-resectable ICC with favorable characteristics for the study of recurrence patterns and mechanisms of metastasis after resection. This model holds great promise for preclinical evaluation of novel multimodal or adjuvant therapies to prevent recurrence and metastasis after R0-resection. (Hepatology 2013;53:1031-1041)
Gesehen am 01.02.2021